KONTRIBUSI PERSEPSI LINGKUNGAN, KOMPETENSI KERJA, DAN K3 TERHADAP KINERJA PEGAWAI - Sugeng Pramudibyo; Yayi Febdia Pradani; Bella Cornelia Tjiptady (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2023)
The high number of work accidents that occur in Indonesia causes many economic losses for both employees and companies. The aims of this study included knowing the effect of OSH implementation on performance, the influence of the work environment on performance, the influence of competence on performance, and the effect of OSH implementation, work environment, and competence on the performance of SMK alumni employees in the AHASS workshop in Malang City. The population in this study were all AHASS workshop mechanics in the city of Malang. Sampling was carried out by proportional random sampling and obtained as many as 118 people. The research design uses a correlational quantitative design. The results showed that there was a significant contribution between K3, work environment, and competency on the performance of SMK alumni employees in the AHASS workshop in Malang City. This is indicated by the contribution value of 63.4%. Partially, the application of OSH contributed 30.22%, perceptions of the work environment contributed 15.12%, and competence contributed 17.8%. So the conclusion from this study is that OSH, work environment, and competence each have an influence on the performance of SMK alumni employees. All three simultaneously have a significant contribution to performance. So it is hoped that the AHASS workshop can create a comfortable and safe work environment for employees, besides that mechanics are also expected to always improve the application of K3 at work.